A checklist of pteridophytes collected on cham chu mountainsand adjacent sites - Loc, Phan Ke; Duong, Vu Thuy; Toan, Vu Cong; The, Pham Van; Bon, Trinh Ngoc (Academia Journal of Biology, 2019)
Located in Tuyen Quang and Ha Giang Provinces, the Cham Chu Nature reserve (NR) has diverse plant ecosystem types, and its the flora is rich in species. However,  the pteridophyte flora of Tuyen Quang and Ha Giang Provinces has not been so far generallystudied. This study presented results of three biotic surveys conducted on Cham Chu mountainsand adjacent sites surveysin 2018−2019. A total of 123 plant specimens gathered and analyzed. with 84 plant species of 43 genera belonging to  23 families recorded. The family Polypodiaceae is therichestwith 8 genera and 12 species. Twogenera, Tectaria and and Pteris, are richin species, with 9 and 8 species, respectively. A checklist of  species was also provided.